Kombinasi Sari Buah Semangka dalam Pengencer Kuning Telur dan Larutan Tris Terhadap Kualitas Spermatozoa Babi Landrace - Potret, Simon Petrus; Marawali, Aloysius; Riwu, Agustinus Ridolf; Kune, Petrus (Yayasan Sumber Daya Manusia Cerdas, 2024)
in egg yolk diluent (EY) on the quality of spermatozoa in landrace pigs. In this study, the semen source was obtained from 1 male landrace pig aged 2 years in healthy condition, and had been trained in semen storage which was then diluted with treatment diluent, namely: T0: WMJ 80%+EY 20%, T1: WMJ 60% +EY 20%+TS 20%, T2: WMJ 40%+EY 20%+TS 40%, T3: WMJ 20%+EY 20%+TS 60%, T4: EY 20%+TS 80%. Diluted semen is stored at 15-20 ̊C and evaluated every 8 hours for motility, viability, abnormalities and survival. The results showed that the diluent WMJ 20%+EY 20%+TS 60% had higher quality (P<0.05) compared to the other four treatments, namely with motility (62.00±2.74%), viability (70.20±2.77%), abnormality (3.30±0.27%) and survival (32.00±0.00) hours. It was concluded that the diluent WMJ 20%+EY 20%+TS 60% could have a good influence in maintaining the quality of spermatozoa in landrace pigs.